2022
DOI: 10.1155/2022/7380632
|View full text |Cite|
|
Sign up to set email alerts
|

To Explore the Application of PDCA in Hemodialysis Center and Its Effect on the Maintenance of Internal Fistula

Abstract: Background. The survey found that in recent years, with the incidence of chronic kidney disease (CKD) increasing, some patients with CKD even progressed to end-stage renal disease. Luckily, progressive hemodialysis technology and nursing level can improve the quality of life and prognosis of patients. Objective. To explore the application of plan-do-check-adjust (PDCA) cycle in the management of nurses in hemodialysis center and its effect on the maintenance of internal fistula in patients. Methods. In this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The PDCA cycle method is more common in nursing management. It is a closedloop management method for sustainable quality improvement [11][12]. In the operation of the whole model, the establishment of an e cient continuous quality improvement team guarantees completion of continuous quality improvement.…”
Section: Discussionmentioning
confidence: 99%
“…The PDCA cycle method is more common in nursing management. It is a closedloop management method for sustainable quality improvement [11][12]. In the operation of the whole model, the establishment of an e cient continuous quality improvement team guarantees completion of continuous quality improvement.…”
Section: Discussionmentioning
confidence: 99%
“…CVC-group: Puncture was done at the right internal jugular vein and tunneled dialysis catheter (Covidien, Inc, USA) placement was performed. Hemodialysis treatment: 11 All patients were required to receive regular dialysis. The dialyzer used was FX80 high-flux dialyzer (Fresenius, Germany), with a membrane area of 1.6 m 2 .…”
Section: Avf-groupmentioning
confidence: 99%
“…[1][2][3] Digestive endoscopy mainly combines chemical and electronic staining techniques to observe lesions, not only improving the clarity of observation, but also increasing the detection rate of digestive tract diseases, with a more prominent effect compared to traditional white light endoscopy. [4,5] However, with the promotion and use of gastrointestinal endoscopy, it has been found in practical work that some patients are prone to trigger negative emotions such as tension, fear, and anxiety due to their low understanding of gastrointestinal endoscopy and significant physiological stress reactions, which directly hinder the development of examination work, and have a certain impact on the outcome of diagnosis and treatment, and may even increase the probability of risk events. [6][7][8] After in-depth clinical research, some studies have found that providing corresponding nursing interventions during the implementation of digestive endoscopy can effectively prevent the occurrence of adverse events, while providing prerequisite guarantee for the smooth completion of diagnosis and treatment.…”
Section: Introductionmentioning
confidence: 99%